Are There Predictors of Success for Students With Disabilities Pursuing Postsecondary Education?. (November 2021) - Madaus, Joseph W.; Gelbar, Nicholas; Dukes, Lyman L.; Taconet, Ashley; Faggella-Luby, Michael
Students with disabilities are entering college in increasing numbers. Despite the increase, college persistence and completion remains a troublesome hurdle. Evidence-based practices and predictors have been identified for secondary-level students with disabilities; however, a parallel classification does not exist for postsecondary education. The purpose of this systematic review was to determine whether there are evidence-based predictors of college success with regard to retention, academic achievement, and graduation. Results indicated that although there are an insufficient number of studies to validate a core set of evidence-based practices at this time, there are a series of student-related practices that positively predict grade point average, retention, and graduation that warrant future investigation.